The TAWOCK conceptual model at content knowledge for professional teaching in vocational education - Zainal Arifin; Muhammad Nurtanto; Warju Warju; Rabiman Rabiman; Nur Kholifah (International Journal of Evaluation and Research in Education (IJERE), 2020)
Now days, the integration of technology in the concept of learning is the trend in global education. The conceptual framework model is a general reference, and the only concept is Technology, Pedagogy, and Content Knowledge (TPACK). However, vocational education has knowledge of specific content, so adjusting conceptual models in professional learning is important to learn and offer. The purpose of this study is to evaluate the concept of TPACK into the concept of vocational education to improve the professionalism of vocational teachers in content knowledge. The author discusses the knowledge structure of vocational fields that are built based on work, content, technology, and the suitability of the learning approach. Based on the results of the article found a new construction in building knowledge in the field of vocational education with special expertise characteristics and shifting pedagogical concepts towards andragogy in learning concept. The results of the analysis recommend the TPACK concept transformed into the Technology, Andragogy, Work, and Content Knowledge (TAWOCK) concept in vocational learning.